If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 = 4(X + -3) Reorder the terms: 16 = 4(-3 + X) 16 = (-3 * 4 + X * 4) 16 = (-12 + 4X) Solving 16 = -12 + 4X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-4X' to each side of the equation. 16 + -4X = -12 + 4X + -4X Combine like terms: 4X + -4X = 0 16 + -4X = -12 + 0 16 + -4X = -12 Add '-16' to each side of the equation. 16 + -16 + -4X = -12 + -16 Combine like terms: 16 + -16 = 0 0 + -4X = -12 + -16 -4X = -12 + -16 Combine like terms: -12 + -16 = -28 -4X = -28 Divide each side by '-4'. X = 7 Simplifying X = 7
| n-14=-20 | | 3p-9=90 | | (x-6-2i)(x-6+2i)=0 | | 120000(x-100)+150((X^2)-400+40000)=22536(600-x) | | 3p-9=180 | | -7(3+6p)+p=12-8p | | -2(d+5)=-4 | | 12y+6=2(6y+1) | | 2(443+88)=56 | | 28+-4x=-64 | | 12x=c+25 | | f(-3)=-2x+3 | | -5(X+3)+2x=45 | | 0.4x-0.8(5-x)=1.4 | | 4x^2-9x+13=8x+9 | | (4a^2-7ab)*2a^3b= | | 3X+9=-4x+25 | | x+(x+200)+3(x+200)=1575 | | C=12x+25findx | | 5(x+5)=-36 | | 3(n-6)+n=4-2(n-1) | | V-9=-10 | | x+(x+200)+3(x+200)=1775 | | 5.2+0.7=2.8+2.2 | | x+(x+200)+3(x+200)= | | -16+y=2y | | 3(z-7)=12 | | 2.49+1.24b=11.17 | | 3g+5=21+g | | 4=-2x+5x+4 | | 3(5)-3x=9 | | 3(2-7)=12 |